The effects of lime solution on the properties of SiO2 nanoparticles binary blended concrete - Abdul Rashid, Suraya; Mohd Salleh, Mohamad Amran; Abd. Aziz, Farah Nora Aznieta; Naji Givi, Alireza (2011)
In this study, the effects of SiO2 nanoparticles on both mechanical properties (compressive, split tensile and flexural strength) and physical properties (water permeability, workability and setting time) of binary blended concrete have been investigated. SiO2 nano-particles have been used as a partial cement replacement by 0.5, 1.0, 1.5 and 2.0 wt.%. Curing of the specimens has been carried out in water and lime solution for 7, 28 and 90 days after casting. For the specimens cured in water, the optimal replacement level of cement by SiO2 nanoparticles for producing concrete with improved strength, was set at 1.0 wt.%. However, by curing the specimens in lime solution, Portland cement could be advantageously replaced by 2.0 wt.% of SiO2 nanoparticles. It was concluded that the SiO2 nanoparticles can improve the filler effect and its ultra high pozzolanic activity causes more C–S–H gel formation when cured in lime solution. Although curing in the lime solution can reduce the strength of control concrete, Curing the specimens containing SiO2 nanoparticles in lime solution causes faster setting time together with higher strength and residence to water absorption.